Sovereign Intelligent Platform Economy on BRICS+ Platform - Bryndin E.G. (Journal of World Economy, 2024)
The sovereignty of the economy of the BRICS+ community is based on intelligent platforms for interaction between users, including commercial transactions and innovative solutions. International platform-based regulated economic interaction on the BRICS+ platform is relevant for the formation of a fair, secure world order. International platform-based regulated economic interaction leads to the formation of technological sovereignty of the BRICS+ countries, to the creation of energy-efficient technologies and energy-optimal proposals to meet demand. An international energy-equivalent economy promotes optimal energy use.